PENERAPAN MODEL PEMBELAJARAN ACTIVE KNOWLEDGE SHARING TERHADAP HASIL BELAJAR TEKNIK INSTALASI LISTRIK - Maya Gustina; Dadang Mulyana (Universitas Negeri Medan, 2023)
Abstract The purpose of this research is to: (1) This study aims to (1) find out the differences in learning outcomes between the use of the Active knowledge sharing model and the use of the Expository model on smart home material. (2) Knowing the effectiveness of applying the Active knowledge sharing model to smart home material in class XI Electrical Lighting Installation Engineering (TITL) Imelda Medan Private Vocational School. This type of research is a quasy experiment with the Active Knowledge Sharing research model. The results showed: (1) the learning outcomes of the Experiment class with the Active Knowledge Sharing model (mean = 83.3; g = 0.6). Higher than the learning outcomes of the Expository Model Control class (mean = 69.2; g = 0.29). (2) The learning outcomes of the Active Knowledge Sharing model (88.57%) are categorized higher than the application of the Expository model (33.3%). Based on the results of the t test from the average value of the posttest obtained t_count is 5.69 and t_table is 2.016692199. Based on hypothesis testing criteria. It can be seen that t_count ˃ t_table and P value < (0.05). Then the hypothesis testing is concluded with Ho being rejected and Hα being accepted. This means that there is a very significant difference in learning outcomes using Active Knowledge Sharing and using Expository. The effectiveness showed that the number of students who achieved the KKM score in the Active knowledge sharing model class was 23 students (88.57%) in the high category, while in the class using the Expository model the number of students who achieved the KKM score was only 11 students (33.3%) with low category. While the use of the Active knowledge sharing model is more effective than the use of the Expository model. Key Words: Learning Outcomes, Active Knowledge Sharing Model Exposito Model AbstrakTujuan Penelitian ini untuk: (1) Penelitian ini bertujuan untuk (1) Mengetahui perbedaan hasil belajar antara penggunaan model Active knowledge sharing dengan penggunaan model Ekspositori pada materi smart home. (2) Mengetahui efektifitas penerapan model Active knowledge sharing pada materi smart home pada kelas XI Teknik Instalasi Penerangan Listrik (TITL) SMK Swasta Imelda Medan. Jenis penelitian ini adalah quasy Eksperimen dengan model penelitian Active Knowledge Sharing. Hasil penelitian menunjukkan: (1) hasil belajar kelas Eksperimen dengan model Active Knowledge Sharing (mean =83,3; g =0,6). Lebih tinggi dibandingkan hasil belajar kelas Kontrol model Ekspositori (mean =69,2; g =0,29). (2) Hasil belajar model Active Knowledge Sharing (88,57%) dikategorikan lebih tinggi dibandingkan dengan penerapan model Ekspositori (33,3%). Berdasarkan hasil uji t dari nilai rata-rata posttest diperoleh adalah 5,69 dan adalah 2,016692199. Berdasarkan kriteria uji hipotesis. Dapat dilihat bahwa ˃ dan P value < (0,05). Maka pengujian hipotesis disimpulkan dengan Ho ditolak dan Hα diterima. Artinya ada perbedaan yang sangat signifikan pada hasil belajar dengan menggunakan Active Knowledge Sharing dengan menggunakan Ekspositri. Efektivitas yang menunjukkan bahwa jumlah siswa yang mencapai nilai KKM pada kelas model Active knowledge sharing adalah 23 siswa (88,57%) dengan kategori tinggi, sedangkan pada kelas penggunaan model Ekspositori jumlah yang mencapai nilai KKM hanya 11 siswa (33,3%) dengan kategori rendah. Sedangkan penggunaaan model Active knowledge shaing lebih efektif dibandingkan dengan penggunaan model Ekspositori. Kata Kunci: Hasil Belajar, model active kknowledge sharing model Eksposito